Characterization and comparison of the grindability, residual compressive strength, and hydrated phases of traditional cement prepared from lime rock and carbide slag. (15th November 2022) - Wang, Qiang; Li, Chuanming; Zhou, WenTao; Lyu, Xianjun
Abstract: Multiplying consumption of traditional cement leads to a consequent surge in demand for lime rock (LR). Carbide slag (CS), a calcium "solid waste", is forced to be produced during the production of acetylene. This work prepared a traditional cement (lime modulus: 0.95, silica modulus: 2.66, and alumina modulus: 1.51) from CS (S-CS) and compared it with that from LR (S-LR) by studying the preparation temperature, mineral phase, residual compressive strength, and hydrated phases and their structure and quantity, as well as analyzing the grindability of CS and LR. Results show that the grinding time for D90 (≤80 μm) of CS is 2 min (saving 76.22% energy compared to LR); 82.30 wt% CS substitutes for 86.39 wt% LR for the preparation of traditional cement without regard to the grinding and transportation, resulting in 0 wt% CO2 emission and the preparation temperature would be reduced by 50 °C (saving 3.47% energy). The mineral phases of S-CS and S-LR are the same in types, but CS for the preparation of traditional cement is beneficial to the formation of Ca3 SiO5 and Ca3 Al2 O6, except for Ca2 SiO4 . Results also show that the hydrated phases of S-CS and S-LR are the block CSH, rod AFt, and layer Ca(OH)2 ; while their quantity in S-CS is higher than that in S-LR, leading that S-CS performs better on the residual compressive strength after 30 times of sulfate resistance dry-wet cycle testing. This work provides a feasible substitute for LR and broadens a resource management method for CS in practice. Highlights: The grinding of carbide slag saves 76.22% energy compared to lime rock. 82.30 wt% carbide slag substitutes for 86.39 wt% lime rock in cement preparation. 50 °C temperature and 3.47% energy are reduced using the carbide slag. Mineral phases, residual compressive strength and hydrated phases are investigated.